Autoantibodies common in patients with gastrointestinal diseases are not found in patients with endometriosis: A cross-sectional study. (September 2019) - Ek, Malin; Roth, Bodil; Valentin, Lil; Nordengren, Johanna; Ohlsson, Bodil
Abstract: Objectives: Gastrointestinal symptoms are common in endometriosis, but the mechanisms behind these symptoms are yet poorly understood. Associations between endometriosis and irritable bowel syndrome (IBS), celiac disease, and various autoimmune diseases have been reported. These diseases express characteristic autoantibodies. The aim of the current study was to investigate autoantibodies against gonadotropin-releasing hormone 1 (GnRH1) and luteinizing hormone (LH) and their receptors, tenascin-C, matrix metalloproteinase-9, deamidated gliadin peptide, and tissue transglutaminase in a cohort of women with endometriosis, compared to controls and women with IBS or enteric dysmotility. Study design: One hundred seventy-two women with laparoscopy-verified endometriosis completed questionnaires regarding socio-demographics, lifestyle habits, medical history, and gastrointestinal symptoms, and sera were analyzed with ELISA for the abovementioned antibodies. Healthy female blood donors (N = 100) served as controls, and women with IBS or enteric dysmotility (N = 29) were used for comparison. Results: A non-significantly higher prevalence of IgM antibodies directed at tenascin-C (7.6% vs. 2.0%; p = 0.06) was the only observed difference in autoantibody levels in endometriosis compared to controls. Antibody presence was not associated with any clinical parameters. Patients with IBS or enteric dysmotility expressed higher levels of IgM antibodies against GnRH1 compared to both patients with endometriosis (p = 0.004) and healthy controls (p = 0.002), and higher levels of tenascin-C antibodies compared to healthy controls (17.2% vs. 2.0%; p = 0.006). Conclusions: Women with endometriosis do not express higher prevalence of autoantibodies found to be characteristic in other patient groups with gastrointestinal symptoms.